Load distribution mechanism of subchondral cancellous bone - T. Harnroongroj (2018)
In order to study the working mechanism of the load distribution of subchondral cancellous bone, a depression osteochondral fracture was created. Two groups of fresh cadaveric femoral condyles were prepared. In group 1, the cancellous bone of the femoral condyle was preserved. In group 2, the cancellous bone of the femoral condyle was removed except for approximately 1.5 cm thickness of the cancellous bone under the articular cartilage. Bone cement was then packed into the femoral condyles to replace the removed cancellous bone. Using the universal testing machine, a uniaxial compression load was applied through a round metal indenter to produce a depression osteochondral fracture. The results revealed that the average load pressure producing osteochondral fracture and the depression depth of the fracture were 27.89 MPa and 1.86 mm in group 1 and 34.05 MPa and 1.83 mm in group 2. Histological study showed that neither group 1 or 2 had articular cartilage injury. In group 1, there was fracture of the subchondral bone plate whereas subchondral cancellous bone was normal. In group 2, the fracture extended more into the subchondral cancellous bone which had interdigitation and compaction of bone trabeculae. In conclusion, subchondral cancellous bone distributes injury load from the articular cartilage by the working mechanism of interdigitation and compaction of bone trabeculae. Therefore, a normal amount of cancellous subchondral bone is important for protection against articular cartilage injury.